1970
DOI: 10.3126/njst.v11i0.4127
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Goat Production Technology at the Farm Level: A Case of Krishnagandaki VDC, Shyangja District

Abstract: Adoption of goat production technology consists of health, breeding, nutrition, pasture and fodder and management. The study was conducted in Krishnagandaki VDC of Syangja district with the objective of exploring the existing goat production technology adoption at the farm level. The methodology of the study included household survey, participatory rural appraisal and secondary data analysis. Most of the farmers raised goats in the villages. Overall farmers reported that the average adoption of goat production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…The average flock size was found to be 5.48±0.15 (Mean ±SE) goats per household with a maximum of 15. The average flock size was similar to findings in Kaski District by Redding et al (2012) whereas Nepali et al (2010) reported that farmers raised an average of 4 goats in Syangja district. Details on goat flock structure is shown in Figure 2.…”
Section: Flock Characteristicssupporting
confidence: 79%
“…The average flock size was found to be 5.48±0.15 (Mean ±SE) goats per household with a maximum of 15. The average flock size was similar to findings in Kaski District by Redding et al (2012) whereas Nepali et al (2010) reported that farmers raised an average of 4 goats in Syangja district. Details on goat flock structure is shown in Figure 2.…”
Section: Flock Characteristicssupporting
confidence: 79%
“…Also, reported the average income from goat sale was estimated to be Rs 11,299 per household (Thakur et al, 2003). Goat production technology is the combination of breeding, health, nutrition, management, pasture, fodder and agro-forestry (Nepali et al, 2010). In this study, housing, feeding, breeding, health and general management aspects were taken to measure the level of adoption.…”
Section: Household Income Analysismentioning
confidence: 99%
“…Утримання кіз у невеликих родинних фермах з кількістю тварин до 100 голів, це дещо інший вид діяльності який ставить за мету не лише споживчі, а певні фінансові цілі. Доречи, такий тип господарювання притаманній багатьом країнам (Dossa, Rischkowsky, Birner, & Wollny, 2008;Nepali et al, 2011;Boz, 2015;Lu, & Miller, 2019;Kaumbata et al, 2020;Gökdai, Sakarya, Contiero, & Gottardo, 2020;Rasyid, Rohani, Aminawar, & Darwis, 2020;Sow et al, 2021).…”
Section: основна частинаunclassified